Modeling Dual-SiOxN Thin-Film Edge Coupler with Ultra-Low Loss and Large Alignment Tolerance - Zhaozhen Chen; Xin Fu; Lei Zhang; Zhengsheng Han (Photonics)
High-performance facet couplers are essential components in the field of silicon nitride integrated photonic chips. In this work, a novel end-face coupling structure, using a double-layer SiOxN thin-film waveguide, is proposed. By precisely controlling the thickness and gap of the SiOxN layers, we achieve flexible tuning of the output mode field size. This structure offers exceptional performance, including ultra-low coupling loss (TE: 0.29 dB, TM: 0.31 dB), large 3 dB alignment tolerance (±2.5 μm), and near-zero polarization-dependent loss. The optimized design strikes a favorable balance between coupling efficiency and alignment tolerance, making it well-suited for a wide range of photonic applications.